(untitled) (Homoeopathy for All, 2024)
Wart is a small growth with a rough texture that can appear anywhere on the body. It can look like a solid blister or a small cauliflower. A small, fleshy bump on the skin or mucous membrane. Warts are benign skin growth that appears when a virus infects the top layer of the skin. And the viruses that cause warts are called human papillomavirus (HPV). Warts can apply anywhere on the skin and are noticed mostly on the hands and feet. They are highly contagious and spread to other areas of the skin as well as spread to others when shared towels, razors etc are used. The skin is where internal diseases manifest. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.